THE EFFECT OF INTERACTIVE LEARNING ON INCREASING THE PROFESSIONAL COMPETENCE OF STUDENTS IN STUDYING THE SCIENCES - Манзій, О.A.; Коробко, О.О. (Modern engineering and innovative technologies, 2024)
The article analyzes the concept of pedagogical technology, interactive technologies. The tasks of interactive learning in the study of natural sciences are defined. The specific principles of interactive learning and the main tasks it accomplishes are hi